Regenerative processes for Poisson zero polytopes - Martínez, Servet; Nagel, Werner (Advances in applied probability, 2018)
Let (Mt:t>0) be a Markov process of tessellations of ℝℓ, and let ( t:t>0) be the process of their zero cells (zero polytopes), which has the same distribution as the corresponding process for Poisson hyperplane tessellations. In the present paper we describe the stationary zero cell process (at at:t∈ℝ),a>1, in terms of some regenerative structure and we show that it is a Bernoulli flow. An important application is to STIT tessellation processes.